PENGEMBANGAN PERPUSTAKAAN SEKOLAH DASAR DI DKI JAKARTA - Rugaiyah Rugaiyah (Universitas Negeri Jakarta, 2011)
Development of libraries in this case focused on elementary school library. The purpose of this study is to determine the condition of the management of primary school libraries in East Jakarta and to obtain information about the strategic development plan for elementary school library in accordance with the standard of school facilities and infrastructure. This study is a survey research using exploratory and descriptive methods. Descriptive method used to analyze the results of questionnaires from respondents about the real conditions of primary school libraries in DKI Jakarta Province in terms of availability of facilities and utilization of library materials and library management. Exploratory method used to analyze the results of interviews from respondents about the development of elementary school library to National Standard of Education. Results of this study are : First, elementary School Library in DKI Jakarta Province has not been managed well. Second, not all state primary school in the provinces of DKI Jakarta has a school library standards. Third, Schools that have a library was not supported by adequate facilities.